1990
DOI: 10.1182/blood.v75.7.1540.1540
|View full text |Cite
|
Sign up to set email alerts
|

The production of transforming growth factor-beta in acute megakaryoblastic leukemia and its possible implications in myelofibrosis

Abstract: Acute myelofibrosis is often associated with acute megakaryoblastic leukemia (AMKBL). Although the exact mechanism for the progression of myelofibrosis in AMKBL is unclear, certain humoral factors from megakaryoblastic cells, the precursors of platelets, may be involved in the enhancement of collagen synthesis by bone marrow fibroblasts. The present study, therefore, is an investigation of the possible pathogenic role of transforming growth factor-beta (TGF-beta), known to be a very potent collagen-stimulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…b). It has been previously demonstrated that the production of platelet-derived growth factor and of TGF-pl is increased in patients affected by myelofibrosis with myeloid metaplasia (Martyre et al, 1991) and in patients with acute megakaryoblastic leukaemia (Terui et al, 1990). Interestingly.…”
Section: Discussionmentioning
confidence: 95%
“…b). It has been previously demonstrated that the production of platelet-derived growth factor and of TGF-pl is increased in patients affected by myelofibrosis with myeloid metaplasia (Martyre et al, 1991) and in patients with acute megakaryoblastic leukaemia (Terui et al, 1990). Interestingly.…”
Section: Discussionmentioning
confidence: 95%
“…32,33 One cause may be increased concentrations of transforming growth factor-beta, a potent promoter of collagen synthesis by bone marrow fibroblasts, which is stored in platelet a granules. 33,34 In canine cases of acute megakaryoblastic leukemia, marrow fibrosis due to accumulation of reticulin or collagen is a variable finding. 10,19 In the present case, no evidence of bone marrow fibrosis was found, although the 2 first failed attempts to obtain a bone marrow aspirate could suggest its presence.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings also suggested that PDGF released from the platelets of some patients with myeloproliferative disorders inappropriately stimulated fibroblasts to divide and secrete collagen. Kimura et al (1988) reported that the growth and stromal protein synthesis of fibroblasts, which cause marrow fibrosis, were stimulated by TGF-b, PDGF and EGF, and Terui et al (1990) observed the production of TGF-b in patients with acute megakaryoblastic leukaemia.…”
Section: Discussionmentioning
confidence: 99%